Analysis of Project Delay Using the Fault Tree Analysis (FTA) Method in Rising Building Projects - Asyari, Saidatul Alfena Putri; Putra, I Nyoman Dita Pahang (CIVED, 2023)
A job on a construction project can affect delays throughout the project. Every construction project has a specific plan and schedule for when to start when to finish, how to schedule, and how to provide resources. There should be no delays in implementation because they will result in increased project costs. However, there was a delay in the performance of the lecture building construction project with the Faculty of Engineering UPN "Veteran" East Java. The methods given in the discussion to determine the factors that influence the occurrence of delays are the Fault Tree Analysis (FTA) method and the Obtain Cut Set Method (MOCUS). Work items that experienced delays were structural, architectural, and MEP work. There are three top events known through FTA analysis, namely delays caused by design changes and wrong drawings, which are factors causing delays from service users. The dominant factor causing delays in structural work is the difference in elevation with elegant buildings and a need for more attention to structural safety. This problem occurs in the top event factor of service users. The service users referred to in scientific research are the owners and/or planning consultants. From the results of a quantitative Fault Tree analysis, the reliability value of the structural work is 0.861. In this case, the structural work experienced a delay of >10% with a Reliability value below 90%, so the contract was declared critical.